Inositol-requiring enzyme 1 alpha is essential for dentinogenesis - Xu, Qian; Liang, Tian; Li, Jiahe; Wang, Suzhen; Zhang, Hua; Hollien, Julie; Iwawaki, Takao; Qin, Chunlin; Lu, Yongbo (Frontiers in Physiology, 2025)
IntroductionInositol-requiring enzyme 1 alpha (IRE1α), encoded by endoplasmic reticulum (ER) to nucleus signaling 1 (Ern1) gene, is the most conserved sensor of ER stress. IRE1α-initiated signaling pathways contribute to functional maturation of secretory cells and have been implicated in various human diseases. In this study, we examined the roles of IRE1α in odontoblast development and dentin formation in wild-type mice as well as in DsppP19L mutant mice, which express a pathogenic variant of dentin sialophosphoprotein (P19L-DSPP) and exhibit a dentinogenesis imperfecta (DGI)-like phenotype.MethodsWestern-blotting and stains-all staining analyses were used to assess whether secretion of mutant P19L-DSPP was impaired in dental pulp cells containing odontoblasts from DsppP19L/P19L mice compared with Dspp+/+ controls. Immunohistochemistry and reverse-transcription PCR were performed to examine changes in IRE1α and its downstream target X-box binding protein 1 (XBP1) in P19L-DSPP mutant mice. To further investigate the roles of IRE1α in tooth development, we generated 2.3 Col1-Cre;Ern1fl/fl and compound 2.3 Col1-Cre;Ern1fl/fl;DsppP19L/+ mice. Structural and histological changes in mandibular molars were analyzed using plain X-ray radiography, micro-computed tomography (µCT), and histology. Additionally, in situ hybridization, quantitative real-time PCR, and immunohistochemistry were performed to compare molecular changes among these mice and Ern1fl/fl and Ern1fl/fl;DsppP19L/+ controls.ResultsWestern-blotting and stains-all staining analyses support that mutant P19L-DSPP protein was not efficiently secreted into dentin matrix and was accumulated within odontoblasts. Further, immunostaining signals for phosphorylated IRE1α and total XBP1 were dramatically increased in odontoblasts and other dental pulp cells of DsppP19L/+ and DsppP19L/P19L mice, in comparison with Dspp+/+ mice. Consistently, there was a small increase in spliced XBP1S protein and Xbp1s mRNA levels in P19L-DSPP mutant mice. Moreover, loss of IRE1α function reduced dentin formation in 2.3 Col1-Cre;Ern1fl/fl mice and exacerbated the dental defects of P19L-DSPP mutant mice. Notably, IRE1α deficiency did not restore the Dspp mRNA levels in the mutant mice but normalized the increased thickness of the dental pulp chamber floor dentin.ConclusionThese findings underscore the essential role of IRE1α in odontoblast function and dentinogenesis. Moreover, they reveal a context-dependent pathogenic role of IRE1α, providing new insights into ER stress in dental tissue development and disease.